Dijitalleşme Ve Türk Sineması - Ormanlı, Okan (The Turkish Online Journal of Design, Art and Communication, 2012)
Until the 1990’s Turkish cinema was considered as a less developed and insufficient cinema in terms of technology. With the rise of private TV channels, the advances in the advertising industry and with the sponsorships and funds of local and foreign foundations, Turkish cinema was able to use the latest technology in the field of cinema. In this context the technical equipments which were used in western cinema were put in to use in the Turkish cinema and with this oppurtunity, even special effects were applied in some big budget movies. Changes in the classical production style led to changes in distribution and viewership trends. This change caused a discussion about how to deal with the old and how to adapt to the new. Now, there is an environment in the cinema industry where analogue technology has nearly completely been replaced by digital technology. Some filmmakers suggest that digital tehnology has led to the democratisation of the Turkish cinema, whereas some cinema critics believe that due to the cheapness of this technology has led to an increase in interest in the film industry and made people believe that anyone could be a filmmaker. The aim of this study is to evaluate the effects of digitalisation in Turkish cinema in terms of production, distribution and spectatorship.
Keywords: Turkish Cinema; Technology; Digitalisation; Türk Sineması; Teknoloji; Sayısallaşma